Teaching English in Rural Area: Difficulties and Strategies - Anggela, Sophia; Warna, Dewi; Sukma, Fitri Alya Okta (Universitas PGRI Adi Buana Surabaya, 2024)
The difficulty of teaching English in rural areas still exists. This study aimed to find out the teachers' difficulties in teaching English at a rural school in South Sumatera and the strategies they employed to overcome those difficulties. A qualitative method with a case study approach was used in this study. The participants in this study were limited to only one teacher. The data were collected using a semi-structured interview with open-ended questions. Then, data from interviews was analyzed using thematic analysis. After analyzing the data, the findings showed that there are four difficulties and strategies in teaching English for rural area. The difficulties were: (1) insufficient infrastructure and facilities; (2) lack of students’ motivation; (3) less opportunity for professional teacher development; and (4) lack of parental support. In accordance with the difficulties, the strategies were: (1) applying teaching methods and procedures with personal funds; (2) giving motivation; (3) trying the best way to get proper training; and (4) promoting effective communication between parents and teachers. Overall, the study's contributions extend beyond the immediate context of rural English education in South Sumatera, providing valuable insights and implications for enhancing educational practices and policies in rural areas more broadly.